2012
DOI: 10.1136/bcr.03.2012.6027
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification of the elbows in a major petrol burn

Abstract: A case of a young man who developed heterotopic ossification (HO) in his elbows following an accident where he sustained petrol burns to over 60% of his body. His injuries necessitated intubation, escharotomies and a protracted intensive care unit stay that was complicated by septicaemia. Several weeks after the injury, he was diagnosed with HO in his right elbow, followed by the left elbow a week later. He was commenced on an non-steroidal anti-inflammatory drug, a long-term course of a bisphosphonate and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Bisphosphonates are generally considered to be antiresorptive agents that induce osteoclast apoptosis and inhibit calcification. Yet some studies have indicated that it may have some preventive effect on heterotopic ossification, although this conclusion is still controversial ( Vasileiadis et al, 2010 ; Zaman, 2012 ). Aside from the first generation, subsequent bisphosphonates generally only affect osteoclasts and thus are less likely to be able to inhibit the production of heterotopic ossification.…”
Section: Clinical Features Of Heterotopic Ossificationmentioning
confidence: 99%
“…Bisphosphonates are generally considered to be antiresorptive agents that induce osteoclast apoptosis and inhibit calcification. Yet some studies have indicated that it may have some preventive effect on heterotopic ossification, although this conclusion is still controversial ( Vasileiadis et al, 2010 ; Zaman, 2012 ). Aside from the first generation, subsequent bisphosphonates generally only affect osteoclasts and thus are less likely to be able to inhibit the production of heterotopic ossification.…”
Section: Clinical Features Of Heterotopic Ossificationmentioning
confidence: 99%
“…Heterotopic ossification refers to the formation of bone in nonosseous tissue in response to longstanding soft-tissue inflammation 87,88 . Heterotopic ossification has occurred in 1% to 3% of 5812 burn patients 89-93 and has been associated with the presence of full-thickness burns 94 , prolonged immobilization, forceful passive physical therapy, and the presence of infection [95][96][97] . Heterotopic ossification occurs across major joints and muscle groups [98][99][100][101] , with the elbow, shoulder, and hip representing the most commonly described sites 81,85,86 .…”
Section: Heterotopic Ossificationmentioning
confidence: 98%
“…5,6 Therefore, it is not surprising that the incidence of HO in military patients is reported to be higher than that in civilians 7 and polytrauma. 4 Initially described in children in 1692 by Patin, 8 HO was first reported within the burns literature in 1957. 9 The prevalence of HO was reported prior to the1990s as 1.2% but is in the range of 0.2-4% 1,[10][11][12] with the incidence increasing in larger mean total body surface area (TBSA) cohorts with increasing survival.…”
Section: Introductionmentioning
confidence: 99%
“…Initially described in children in 1692 by Patin, 8 HO was first reported within the burns literature in 1957. 9 The prevalence of HO was reported prior to the1990s as 1.2% but is in the range of 0.2–4% 1,10–12 with the incidence increasing in larger mean total body surface area (TBSA) cohorts with increasing survival.…”
Section: Introductionmentioning
confidence: 99%